KOMUNIKASI PERANGKAT NAGARI DAN PARTISIPASI MASYARAKAT DALAM PENGELOLAAN DANA DESA - Listyawati, Dewi; Sarmiati, Sarmiati; Asmawi, Asmawi (Faculty of SociaI and Political Sciences (FISIP), Universitas Islam Negeri (UIN) Bandung, 2019)
There is distrust and suspicion between the community and the nagari government in managing village funds. The nagari tool argues that the community does not care about managing village funds if the funds do not directly touch the community. While the community does not understand the village fund program and has very little curiosity about the distribution of village funds. According to residents, village funds are only for nagari devices and for the people around them and the development that has been done is considered not to come from village funds. Communication solutions to these problems include providing more understanding to the community of the Nagari government. They should more often disseminate information about village funds and programs that will be implemented to the village community. Those who work as nagari devices should be people with adequate education and ability to deal with problems related to village funds, for example the ability to prepare village fund reports or provide good services and information to the community. The community should care about the village fund program and the development program that will be implemented, participate in the village meetings held.